El verbo del corazón en el oficio de sabio - Comas, Abel Miró (Sapientia, 2018)
The office of sage, which is what Aquinate identifies with the mission of his whole life, consists mainly of two operations: the internal contemplation of the truth about God and the external manifestation of this contemplation, either by exposing the aforementioned truth, either refuting the errors contrary to it. These two operations accord perfectly with the nature of our understanding, which tends to manifest and declare in a "verb of the heart" what it is being understood in act. From this perspective, teaching is not understood as an addition that wisdom can come to contemplation, but, rather, as the realization of its intrinsic tendency to communicate, to manifest itself; that is, as the consummation of their tendency to "dialogue".